2016
DOI: 10.1002/bmc.3793
|View full text |Cite
|
Sign up to set email alerts
|

An LC–MS/MS method for rapid and sensitive high‐throughput simultaneous determination of various protein kinase inhibitors in human plasma

Abstract: A reliable, high-throughput and sensitive LC-MS/MS procedure was developed and validated for the determination of five tyrosine kinase inhibitors in human plasma. Following their extraction from human plasma, samples were eluted on a RP Luna®-PFP 100 Å column using a mobile phase system composed of acetonitrile and 0.01 m ammonium formate in water (pH ~4.1) with a ratio of (50:50, v/v) flowing at 0.3 mL min . The mass spectrometer was operating with electrospray ionization in the positive ion multiple reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 60 publications
3
30
1
Order By: Relevance
“…Acetonitrile with ammonium acetate buffer gave better sensitivity and sharper peaks for TOF and TOF‐13C3 15 N than methanol. It was observed that equal proportions of aqueous and organic media in the mobile phase resulted in early elution of TOF as observed previously (Abdelhameed et al, ; Kadi et al, ) on Gemini C 18 and Cosmosil C 18 columns with considerable matrix interference. Further, when the aqueous phase was kept at ≥60%, there was excessive retention of TOF leading to an analysis time of ~10 min.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Acetonitrile with ammonium acetate buffer gave better sensitivity and sharper peaks for TOF and TOF‐13C3 15 N than methanol. It was observed that equal proportions of aqueous and organic media in the mobile phase resulted in early elution of TOF as observed previously (Abdelhameed et al, ; Kadi et al, ) on Gemini C 18 and Cosmosil C 18 columns with considerable matrix interference. Further, when the aqueous phase was kept at ≥60%, there was excessive retention of TOF leading to an analysis time of ~10 min.…”
Section: Resultssupporting
confidence: 80%
“…However, the recovery obtained was <70% and selectivity was significantly affected with considerable matrix interference owing to repeated clogging of the column. Kadi et al () and Abdelhameed et al () reported a mean recovery of ≥98% for TOF from 1000 μL of plasma by LLE with diethyl ether in the presence of glycine buffer. Thus, LLE was tested with different solvents like diethyl ether, ethyl acetate, n ‐hexane, dichloromethane and MTBE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous LC–MS/MS methods have been described for quantification of the individual compounds or a combination of cobimetinib (Cardoso et al, ; Deng et al, ; Huynh et al, ; Rousset et al, ), cabozantinib (Abdelhameed, Attwa, & Kadi, ), dabrafenib (Cardoso et al, ; Huynh et al, ; Merienne et al, ; Rousset et al, ), niraparib (van Andel et al, ), olaparib (Nijenhuis, Lucas, Rosing, Schellens, & Beijnen, ; Pressiat et al, ), vemurafenib (Cardoso et al, ; Huynh et al, ; Nijenhuis, Rosing, Schellens, & Beijnen, ; Rousset et al, ) and regorafenib (Cardoso et al, ; Huynh et al, ; Luethi et al, ; Merienne et al, ; van Erp et al, ) in human plasma. However, a quantification method combining all of the above mentioned oncolytics in a single run has not been published yet.…”
Section: Introductionmentioning
confidence: 99%